(untitled) (Proceedings of International Educators Conference, 2023)
This research study delves into the intricate relationship between global market trends and the investment strategies employed by commercial banks. In an increasingly interconnected world, the dynamics of international markets significantly impact the decision-making processes of financial institutions. The investigation encompasses an analysis of diverse global factors, ranging from geopolitical events to economic shifts, and their direct influence on how commercial banks formulate, adjust, and optimize their investment strategies. By examining real-world case studies and historical data, this research aims to provide valuable insights into the adaptive measures and strategic responses adopted by commercial banks to navigate the ever-changing landscape of global market trends.